Gender and Equal Marriage from a Buddhist Political Science Perspective: Gender and Equal Marriage from a Buddhist Political Science Perspective - Pochailar, Pornpimol; Tho-un, Worachet (RATANABUTH JOURNAL, 2024)
The purpose of this article is to reflect on the perspective of gender equality, despite the fact gender equality is widely accepted and internationally recognized as a fundamental human right aligned with sustainable development goal 5, achieving gender equality and empowering all women and girls. While the constitution of the Kingdom of Thailand has recognized gender equality and prohibits discrimination based on birth, gender identity, and religion, achieving true gender equality requires mechanisms and measures to create a more equitable foundation. marriage of individuals with diverse sexual orientations is not limited solely to men and women but encompasses all gender identities and sexual orientations. This ensures legal protection under principles of equality and human dignity, granting rights such as marriage, marriage registration, management of marital property, representation in criminal matters as well as the spouse, inheritance upon the death of a spouse, adoption of children, inheritance as a legal heir, and entitlement to state welfare benefits as spouses. This includes benefits such as social security compensation and medical expenses, along with other legal rights recognized for married couples.